Molluscicidal activity of Bonga-bonga (Alternanthera sessilis (L.) R. Br. ex DC.) plant extract against Oncomelania quadrasi (Mollendorff, 1895). - Caparro, Allan Christine C. (Allan Christine C. Caparro, 2019)
Oncomelania quadrasi snail, an intermediate host for Schistosoma japonicum is a causative agent of Schistosomiasis remains a public health concern in the Philippines. Synthetic molluscicide threatens non target organism for possible intoxication, thus, the need to find a cheaper and less polluting molluscicides has been considered to substitute in controlling the increasing cases of schistosomiasis. In this study, Alternanthera sessilis methanolic extract was screened for its molluscicidal activity against O. quadrasi. It was evaluated by subjecting snails in a group of 100 in the plant extract with varying concentration ranging from 100ppm-200ppm with 20ppm increments. The methanolic extract showed a promising result of a median lethal concentration (LC50) of 93.33mg/L and (LC90) of 151.36mg/L. This study recommends to conduct three trials with the same concentrations and compare the molluscicidal activity in the different parts of the plant.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.